The allure of the unknown in a tamed, mapped, and homogenized world. (18th November 2022) - Gabora, Liane; Gomez, Isabel
Abstract: As the physical world becomes tamed and mapped out, opportunities to experience the unknown become rarer; imaginary worlds provide a much-needed sense of potentiality. Potentiality is central to the Self-Other Re-organization theory of cultural evolution, which postulates that creativity fuels cumulative cultural change. We point to evidence that fear affects, not the magnitude of exploration, but how cautiously it proceeds.